PENERAPAN ASUHAN KEPERAWATAN KELUARGA DENGAN METODE PSIKOEDUKASI DALAM MENINGKATKAN PENGETAHUAN PERILAKU SEKS PADA REMAJA RW 016 DESA SUMBERJAYA - Salma Nur Shohimah (2022)
During adolescence, a person will move from childhood to adulthood. When they are teenagers, they will begin to know dating. Dating is one of the risk behaviors for adolescents to engage in active sexual behavior. This sexual behavior must be avoided so that the purpose of this study is to provide knowledge of adolescents using psychoeducational methods in increasing knowledge of sexual behavior in adolescents. Psychoeducation intervention was given to two teenagers in RW 016 who had low knowledge of sexual behavior. The implementation of the psychoeducational intervention was carried out on february 14-16, 2022 and was carried out with a duration of 60 minutes in each meeting. The results of the implementation of the psychoeducational intervention showed that after the psychoeducation intervention was carried out 3 times, the score of knowledge of sexual behavior in two teenagers increased. The first teenager experienced an increase from the pretest results of 60%, namely sufficient knowledge to 92% during the posttest, which means that knowledge increased to be good. And the second teenager also increased from the pretest result of 57%, namely sufficient knowledge to 86% or good knowledge. Both teenagers have an increase and there is an influence with psychoeducational methods in increasing sex knowledge in adolescents. Community nurses are expected to be able to use psychoeducational methods in increasing knowledge of sexual behavior in adolescents.